“La vieja sirena": la reinterpretación del mito de la sirena en la novela de José Luis Sampedro - Maceiras Lafuente, Andrea (Amaltea. Revista de Mitocrítica, 2014)
“La vieja sirena": la reinterpretación del mito de la sirena  en la novela de José Luis Sampedro